Thermoeconomic optimization with PSO algorithm of waste heat recovery systems based on organic Rankine cycle system for a natural gas engine (2019)
To contribute to the economic viability of waste heat recovery systems application based on the organic Rankine cycle (ORC) under real operation condition of natural gas engines, this article presents a thermoeconomic optimization results using the particle swarm optimization (PSO) algorithm of a simple ORC (SORC), regenerative ORC (RORC), and double-stage ORC (DORC) integrated to a GE Jenbacher engine type 6, which have not been reported in the literature. Thermoeconomic modeling was proposed for the studied configurations to integrate the exergetic analysis with economic considerations, allowing to reduce the thermoeconomic indicators that most influence the cash flow of the project. The greatest opportunities for improvement were obtained for the DORC, where the results for maximizing net power allowed the maximum value of 99.52 kW, with 85% and 80% efficiencies in the pump and turbine, respectively, while the pinch point temperatures of the evaporator and condenser must be 35 and 16 ◦C. This study serves as a guide for future research focused on the thermoeconomic performance optimization of an ORC integrated into a natural gas engine.